The perfect trio to decrease mortality in pancreatic cancers: Molecular marker screening tests with biosensors in precancerous lesions - Hasan Zafer Acar; Nazmi Özer (Asian Journal of Medical Sciences, 2023)
The mortality rates of pancreatic cancer (PC) are very high. The methods recommended in the studies conducted to date have been able to reduce mortality very little. This study aimed to review studies on this subject and to identify the most appropriate methods to decrease mortality in PCs. Therefore, research articles and reviews on this subject were analyzed intensely, and the findings were summarized. According to the results obtained in our study, to decrease mortality in pancreatic ductal adenocarcinomas, early diagnostic screening should be performed primarily with molecular markers and biosensors effective in precancerous lesions in risk groups. However, studies on such screening worldwide have not yet been conducted. Therefore, further research is needed to arrive at more precise conclusions.